Harmonizing National-International Investment Laws For Indonesian Society Welfare Realization - Eva Arief; Ema Nurhayati (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
This research analyzes harmonization efforts between Indonesian national law and international agreements in the investment field as an instrument to realize societal welfare. This study is normative juridical research with statutory, conceptual, and comparative approaches. The research method was conducted through literature study of primary, secondary, and tertiary legal materials analyzed qualitatively. The research results show disharmony between national investment regulations and Indonesia's commitments in international agreements, particularly in aspects of non-discriminatory treatment, protection of foreign investors, profit repatriation, and investment dispute resolution mechanisms. The main obstacles to harmonization include inconsistent interpretation of international agreement provisions in national court decisions and overlapping authorities between state institutions in implementing international commitments. The research found that the implementation process of international investment agreements into national law remains partial and fragmentary, thus creating legal uncertainty for investors. Consequently, investment targets that can promote societal welfare are not achieved optimally. The research suggests four key recommendations for harmonizing Indonesia's investment law: (1) revising Law No. 25 of 2007 to better integrate international investor protection standards while preserving national policy flexibility, (2) establishing inter-ministerial coordination mechanisms between the Ministry of Law and Human Rights, Ministry of Foreign Affairs, and BKPM to ensure policy coherence, (3) developing an Indonesian bilateral investment treaty model that balances investor protection with adequate regulatory space for public welfare, and (4) harmonizing sectoral regulations with investment law and international commitments to eliminate policy inconsistencies and legal uncertainty for investors, all implemented through a phased approach that prioritizes welfare-oriented investment governance while maintaining international credibility.